Alcohol use disorder among prisoners in Debre Berhan prison, Ethiopia: a cross-sectional study - Yohannes Gebreegziabhere Haile; Kaleab Berhanu Kebede; Asnake Limenhe; Kassahun Habatmu; Atalay Alem (BMC, 2020)
Abstract Background Several studies reported that history of alcohol use among prisoners is higher than the prevalence in the general population. Criminality is found to be associated with alcohol use disorder (AUD) in previous studies. In Ethiopia, there is limited information on the prevalence and associated factors of AUD among prisoners. Therefore, this study aimed to assess the prevalence and associated factors of AUD among prisoners of Debre Berhan Prison. Methods A cross-sectional survey was conducted to assess history of AUD among prisoners at Debre Berhan Prison, before imprisonment. We selected 347 prisoners with a systematic sampling technique and interviewed using Alcohol Use Disorder Identification Test (AUDIT) to screen for AUD in May 2017. Data entry was done using Epi-Data version 3.1 software, and bivariate and multivariate analyses were done using Stata version 13 software. Crude and adjusted odds ratios, with 95% confidence intervals and p-values are reported. Results About six out of ten prisoners (59.1%) had AUD before imprisonment. Factors associated with increased odds of AUD were perception that the current offence is related to using substances (AOR = 4.2; 95% CI = 2.3, 7.8), and family history of substance use (AOR = 8.7; 95% CI = 1.7, 44.9). Being married had lower odds of AUD compared to the unmarried (AOR = 0.5; 95% CI = 0.2, 0.9). Conclusion We found that the prevalence of AUD 1 year before imprisonment in this population is high. AUD is found to be associated with a family history of substance use and perception that the current offence is related to using a substance. We recommend community-based study with different kind of study designs to see the relationship between AUD and crime for planning interventions.